Cost Price Characteristics of Seaport and River Port Services - Perić, Teodor; Vojnović, Savo (Promet - Traffic&Transportation, 2003)
The discussion about the various aspects of the cost price ofthe respective services starts from the previous knowledge aboutthe role and significance of the sea and river ports within thetraffic system, and the scope of their services. The previousknowledge includes also the knowledge about the used meansof long-term assets which are in this study classified into followingthree groups: a) objects of infrast/Ucture, b) objects ofsuprast/Ucture, and c) shopfloors and equipment.The st/Ucture and functional purpose of these means confirmsthe high capital intensity of the sea and river port terminals,which leads to the high share of the fixed components ofthe costs in the cost price of these services.Most of the definitions of the cost price start from the factthat it is a part of the value or price of production, i.e. services,which accounts for the price of the used means (raw materialsand ftxed capital) and the price of the labour.The procedure of obtaining the cost price is called calculation,and certain 1Ules or principles starting from punctuality,adaptability, updating, comparability, economic efficiency, etc.need to be complied with.Due to very high fragmentation of the sea and river port services,it is difficult to hannonise all the mentioned principles,and in calculating the full cost price various methods for calculatingthe common costs are applied, and the suitable methodsof distributing the common costs, i.e. overheads. In order tocalculate these procedures as precisely as possible, appropriateindicators are used, i.e. indirect indicators, but everythingwould be much simpler if the differentiation were narrower, i.e.if the number of given services were reduced by an adequateprocedure of levelling out.